Numerical Investigation and Performance Evaluation of Boiling Slug Flow Regime of Water Vapor in Vertical Tubes - F. Sharifi; M. Hassani; R. Kouhikamali (Journal of Applied Fluid Mechanics)
The boiling phenomenon and two-phase flow regimes have provoked extensive research due to the increased heat transfer coefficient and significant industrial applications. In order to model correct heat transfer of boiling, it is important to simulate its nucleation sites. In this work, boiling phenomenon simulation is carried out numerically in a vertical tube. The operating fluid is water which enters the tube with upward flow at saturated condition. Numerical investigation is carried out by Eulerian-Eulerian volume of fluid model in two-dimensional coordinate system. Slug flow simulation has been conducted by numerically simulating the embryonic bubbly flow at the beginning part of the tube and slugs have been created after formation of nucleation sites. To do so, heat and mass transfer during the flow motion is considered by the rate of mass and energy exchange between the phases and is added to governing equations. One of the key outputs of the numerical simulation is accomplishment of boiling slug flow pattern. Correspondingly, hydrodynamic and heat transfer characteristics of boiling flow regime like bubble detachment location, slug shape and size, local and average heat transfer coefficient are investigated. Furthermore, the effects of Reynolds and Boiling numbers have been studied. Reynolds number in the range of 27000 to 101000 has been considered. It is found that by doubling the Reynolds number, a 36% increase in mean heat transfer coefficient is observed. Additionally increase in the Boiling number by 60%, leads to 3% increase in the mean heat transfer coefficient.